Workplace Protections and Burnout Among Brazilian Frontline Health Care Professionals During the COVID-19 Pandemic - Pereira-Lima, Karina; Loureiro, Sonia Regina; Silveira, Isabella Lara Machado; Crippa, José Alexandre; Hallak, Jaime Eduardo Cecílio; Zuardi, Antonio Waldo; Osório, Flávia de Lima (Frontiers in Psychology, 2022)
Health care workers from low- and middle-income countries have been playing a critical role in overcoming the challenges related to the COVID-19 pandemic; yet little is known about the relationship between workplace protections and well-being of Brazilian health care workers during the pandemic. This study aimed to evaluate whether Brazilian health care workers were satisfied with their workplace measures to protect their physical and mental health during the pandemic, and to assess the associations of such levels of satisfaction with indicators of burnout. Licensed Brazilian health care professionals were recruited via popular media between 5/19/2020 and 8/23/2020 to complete an online survey including questions about their demographic/professional characteristics, satisfaction with their workplace protective measures during the pandemic, and validated questionnaires assessing neuroticism, resilient coping, and symptoms of burnout. Most participants reported being dissatisfied with their workplace measures to protect their physical (516, 56.3%) and mental health (756, 82.5%). In multivariable analysis adjusted for personal and environmental factors, dissatisfaction with workplace physical health protections was significantly associated with higher levels of emotional exhaustion (B=1.08, 95% CI=.47 – 1.69) and depersonalization (B=.61, 95% CI .10 – 1.12), and dissatisfaction with workplace mental health protections significantly associated with higher levels emotional exhaustion (B=1.17, 95% CI=.40 – 1.95). Efforts to improve both physical and mental health protective measures are critical to guarantee that health care workers continue to provide care at their maximum capacity.